Augmented reality, virtual reality, and computer graphics. 5th International Conference, AVR 2018, Otranto, Italy, June 24-27, 2018, Proceedings /: 5th International Conference, AVR 2018, Otranto, Italy, June 24-27, 2018, Proceedings. Part I : (2018) - Unknown
No abstract available